The conservative treatment of congenital scoliosis with hemivertebra: Report of three cases - Caredda, Matteo; Bandinelli, Diletta; Falciglia, Francesco; Giordano, Marco; Aulisa, Angelo Gabriele (Frontiers in Pediatrics, 2022)
Introduction Scoliosis is the most common type of congenital vertebral disease. This spinal disorder may be due to a failure of formation, segmentation, or a combination thereof. Complete failure of formation causes hemivertebra which can lead to unbalanced growth and deformation. Statistically, 25% of congenital curves do not evolve, 25% progress slightly, while the remaining 50% develop quickly and require treatment. Hemivertebrae can be divided into three types: non-segmented, semi-segmented, and fully-segmented. The fully-segmented types are most likely to progress. Hemivertebra in the thoracolumbar region shows higher rates of progression compared with those in the lumbar area. The treatment may be either conservative or surgical. In general, bracing is not recommended in short and rigid curves, although it may help process secondary curves. Objective To assess the effectiveness of bracing in congenital scoliosis due to hemivertebra. Cases presentation Searching in our database, we found three cases of patients with congenital scoliosis due to fully-segmented hemivertebra. The first of them was 6 years old at the time of diagnosis with a fully-segmented hemivertebra in L5, determining an L1-L5 (S1) lumbar curve. The second one was 10 years old at the time of diagnosis with a fully-segmented hemivertebra in L2 and a T11-L4 (L5 sacralized) thoracolumbar curve. The last one was 3 years old at the time of diagnosis with a fully-segmented hemivertebra in L3 (in six lumbar bodies), determining a thoracolumbar curve T12-L4. Results We utilized a Milwaukee brace for the first patient, a Boston brace for the second patient, and a Progressive Action Short Brace (PASB) for the third patient. At the beginning of the treatment, the Cobb angles measured 23°, 53°, and 25°, respectively. During treatment, the Cobb angles measured 22°, 35°, and 15°, respectively. At the end of treatment, the Cobb angles measured 18°, 45°, and 12°, respectively. At long-term follow-up, the curves measured 20°, 45°, and 12° Cobb angles, respectively. Conclusions Comparing our cases with those found in the literature we can confirm the ability of conservative treatment to change the natural history of congenital lumbar scoliosis due to failure of formation. From our experience, in all cases of CS with hemivertebra, before considering a surgical approach, conservative treatment should be implemented as early as possible without waiting for the progressive deformation of the adjacent normal vertebrae.